An investigation on the use of alternative shapes to determine the applicable strain energy function for nearly-incompressible hyperelastic materials - Senador, Antonio E. (1999)
Different assumptions on the nature of the mechaninsm involved in the deformation of hyperelastic materials have led to a number of different proposals for the functional form of the strain energy function. The proponents of each form employed different methods to fit their function on the experimental data, and they used different measures to assess the capability of these fitted models to predict the material behavior in other deformation modes. This investigation proposes another measure for assessment, which would subsequently lead to the selection of the best strain energy function to represent the actual material behavior.
The deformation of the sheet-with-hole and trapezoidal-sheet geometries were modelled in the ANSYS v5.0a finite-element program, using the James-Green-Simpson [1975] data as source of the material parameters. From the result of the simulation (1) the ability of these two geometries to bring out the differences between the functional forms of the strain energy function was assessed; (2) some criteria for the selection of another candidate geometry were pointed out; (3) the applicability of the finite-element method to simulate the test, as well as weaknesses of the formulation in ANSYS, were examined; and (4) a general procedure for the use of alternative geometries to select the most suitable strain energy function was laid out. However, since only numerical simulations were done, actual experiments that will use the results of this study as guide wire recommended to be performed in the future.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Strains and stresses; Deformations (Mechanics); Elastic solids